Induction Motor Monitoring System Base on Fuzzy Logic Controller - Sari Hartati, Prof. Rukmi; Manuaba, Ida Bagus Gede; Mataram, I Made (Journal of Electrical, Electronics and Informatics; Vol 4 No 1 (2020): JEEI (February 2020)DO - 10.24843/JEEI.2020.v04.i01.p03, 2020)
Squirrel cage induction motor is an AC electric motor that is most widely used in industry. This type of motor is chosen because it does not have a commutation brush, and its construction is strong, so it can withstand large, easy flow surges for repair and maintenance. The problem that often occurs is the imbalance of supply voltage which causes motor efficiency to decrease. An imbalance of voltage will result in a current not equal. As a result of phase currents that are much larger than other phases result in an increase in temperature and speed on the motor. This research was conducted to monitor the induction motor so that it can determine the condition of the motor when receiving a voltage imbalance. The method used in the induction motor condition monitoring system is the fuzzy logic method. Parameters that can be monitored are categorized into three conditions: normal (good) motor condition, damage (serious) and serious damage.